Determination of shoulder range of motion - Ho, Qian Ci (2018)
All upper extremity movements involve the shoulder joint, and the shoulder is integral to activities of daily living (ADL) which include drinking, dressing and personal grooming. The system of orthogonal planes is used to describe human bodily movements. Shoulder movement in the sagittal plane is referred to as flexion and extension, while movement in the coronal plane is referred to as abduction and adduction, and rotation about the longitudinal axis of the humerus is referred to as internal and external rotation. Transverse plane is not commonly used in describing shoulder movement. This system enables clinicians to describe the shoulder’s range of motion (ROM) as a method to assess the function of the shoulder. However, the orthogonal plane system is inadequate in describing ADL, which is not limited to these planes of movement. The globe model was introduced to quantify shoulder ROM and is used to accurately describe ADL movement in a more intuitive manner. The objective of this study is to quantify shoulder ROM and ADL utilising the globe model. A total of 40 male subjects with a mean age of 23.8 ± 1.5 years were tasked to do eight standard ROMs, eight ADLs and one extreme range of motion (EROM). Retroreflective markers were attached on bony landmarks of the shoulder joint and humerus, as recommended by International Society of Biomechanics (ISB). An optical motion capture system was used to capture the subjects’ movement. The data collected from the movement of the subjects was calculated using Euler angles to derive shoulder joint angles. The shoulder joint angles were represented by plane of elevation and angle of elevation in the globe model. The results of ADLs, ROMs and EROM were plotted on the globe model using MATLAB. The movements of ADLs were within the EROM, which proved that lesser ROM is needed for ADL. The globe model, therefore, allows better visualisation of shoulder movements as compared to the orthogonal system. This would serve as a useful and more intuitive tool for clinicians to quantify shoulder function and to assess ADLs.